Multiple Trophic Markers Trace Dietary Carbon Sources in Barents Sea Zooplankton During Late Summer - Kohlbach, Doreen; Hop, Haakon; Wold, Anette; Schmidt, Katrin; Smik, Lukas; Belt, Simon T.; Keck Al-Habahbeh, Amalia; Woll, Matthias; Graeve, Martin; Dąbrowska, Anna Maria; Tatarek, Agnieszka; Atkinson, Angus; et al. (Frontiers in Marine Science, 2021)
We investigated diets of 24 Barents Sea zooplankton taxa to understand pelagic food-web processes during late summer, including the importance of sea ice algae-produced carbon. This was achieved by combining insights derived from multiple and complementary trophic marker approaches to construct individual aspects of feeding. Specifically, we determined proportions of algal-produced fatty acids (FAs) to reflect the reliance on diatom- versus dinoflagellate-derived carbon, highly branched isoprenoid (HBI) lipids that distinguish between ice-associated and pelagic carbon sources, and sterols to indicate the degree of carnivory. Copepods had the strongest diatom signal based on FAs, while a lack of sea ice algae-associated HBIs (IP25, IPSO25) suggested that they fed on pelagic rather than ice-associated diatoms. The amphipod Themisto libellula and the ctenophores Beroë cucumis and Mertensia ovum had a higher contribution of dinoflagellate-produced FAs. There was a high degree of carnivory in this food web, as indicated by the FA carnivory index 18:1(n−9)/18:1(n−7) (mean value < 1 only in the pteropod Clione limacina), the presence of copepod-associated FAs in most of the taxa, and the absence of algal-produced HBIs in small copepod taxa, such as Oithona similis and Pseudocalanus spp. The coherence between concentrations of HBIs and phytosterols within individuals suggested that phytosterols provide a good additional indication for algal ingestion. Sea ice algae-associated HBIs were detected in six zooplankton species (occurring in krill, amphipods, pteropods, and appendicularians), indicating an overall low to moderate contribution of ice-associated carbon from late-summer sea ice to pelagic consumption. The unexpected occurrence of ice-derived HBIs in pteropods and appendicularians, however, suggests an importance of sedimenting ice-derived material at least for filter feeders within the water column at this time of year.